Ethical Aspects of Euthanasia. Introduction to the Debate - Karol Bajda (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2019)
The subject of the study is the ethical aspects of euthanasia. The framework of the article does not allow for a comprehensive and complex analysis of the issue presented in the title. In view of the above, the purpose of the article has been limited to two aspects. The first one is the clarification of terminology and an attempt to draw out the classification of euthanasia. The second one is showing the arguments that supporters and antagonists take in the ongoing debate on the subject of euthanasia. In the author’s opinion, the subject that strictly corresponds to the subject matter in the study remains the legal regulations of individual countries regarding euthanasia. This issue has been highlighted at the end of the article and may constitute a contribution to the discussion.